Business as usual: Bank climate commitments, lending, and engagement - Parinitha Sastry; Emil Verner; David Marqués Ibá\~nez (European Central Bank (ECB), 2024)
This paper studies the impact of voluntary climate commitments by banks on their lending activity. We use administrative data on the universe of bank lending from 19 European countries. There is strong selection into commitments, with increased participation by the largest banks and banks with the most pre-existing exposure to high-polluting industries. Setting a commitment leads to a boost in a lender's ESG rating. Lenders reduce credit in sectors they have targeted as high priority for decarbonization. However, climate-aligned banks do not change their lending or loan pricing differentially compared to banks without climate commitments, suggesting they are not actively divesting. We can reject that climate-aligned lenders divest from firms in targeted sectors by more than 2.6%. Firm borrowers are no more likely to set climate targets after their lender sets a climate target, which casts doubt on active engagement by lenders. These results call into question the efficacy of voluntary commitments.
Keywords: Q50; G21; 330; Banks; Green Lending; Voluntary targets